To study the hypotensive and hypolipidemic effects of garlic in smokers in the North Indian population - Kumar, Jayballabh; Kumar, Gaurav; Khan, Farhan Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: Garlic, latin name Allium Sativum, belongs to the onion family Alliaceae, have been widely recognized as agents for prevention and treatment of cardiovascular and other metabolic diseases like atherosclerosis, hyperlipidemia, thrombosis, hypertension and diabetes. Methods: This prospective study conducted on male smokers (n=40) in the department of physiology of Teerthanker Mahaveer Medical College & Research Centre. Selected smokers were further evaluated before and after giving raw fresh garlic weighing about 5-6gm daily for a month. Sample 1:- Before taking garlic parameters. Sample 2:- After taking garlic parameters. After one month all the parameters were analyzed and compared with the baseline parameters. Results: Garlic has a significant hypotensive effect by lowering DBP, SBP also lowered but it was not statistically significant. Also hypolipidemic effects of garlic were found to be statically significant in cases of triglyceride, HDL & LDL, but changes in cases of cholesterol and VLDL are not statically significant. Conclusions: Garlic being hypotensive and hypolipidemic in nature as shown in our study, therefore it can be concluded that garlic is beneficial for human beings. Its main beneficial effect for decreasing the lipid levels as well as the blood pressure in smokers.